Deformation Analysis of a New Subway Transfer Channel Closely Undercrossing an Existing Station - Houqiang Sun; Jun Wu; Jiabing Zhang; Yu Du; Lirong Teng; Houtong Qin (Advances in Civil Engineering)
Disturbances that occur due to the construction of new subway transfer channels in cities pose a significant threat to the safe operation and structural stability of existing subway stations. Due to the construction of the new Jin-Fu Station of Chengdu Rail Transit Line 27, the transfer channel of the new Jin-Fu Station closely underpasses the station of the existing Metro Line 6. First, based on the random medium theory, the curved integral boundaries of the rectangular section are improved and simplified by the numerical simulation. Second, the mechanical response of the underpass construction to the existing subway station is analyzed by Pasternak foundation model theory. Finally, the accuracy of the theoretical calculation is verified by the three-dimensional numerical calculation and the measured data, and the sensitivity of its parameters is analyzed. The results show that maintaining a certain net distance d (that is, increasing the thickness of the interlayer soil) is conducive to forming the soil arch effect and reducing the deformation of the existing station above. The settlement of the existing station can be reduced by increasing the height-to-width ratio of the excavated section, but the maximum bending moment of the floor will increase slightly. With the increase in the foundation reaction coefficient k, the interaction between the soil mass and the existing station is enhanced, and the deformation, bending moment, and shear force on the floor of the existing station increase significantly. When the foundation reaction coefficient increases to 10k, there is an obvious uplift phenomenon outside the settlement trough of the existing station floor.